Design Science Research of weft-knitting spacer project for users with genodermatoses (Revista de Ensino em Artes, Moda e Design, 2025)
This study proposes a methodology based on Design Science Research (DSR) to systematize the development of spacer weave fabrics for biomedical applications, with an emphasis on apparel for patients with Epidermolysis Bullosa (EB) and other genodermatoses. The specific objectives include facilitating designers' technical understanding of the production process and contributing to the teaching of technical textile structures. The research adopts a qualitative, applied approach, utilizing the DSR model proposed by Pimentel, Filippo, and Santos (2020). Textile design software (Raynen) and electronic rectilinear looms were used for prototyping. Spacer weave prototypes were developed based on structural parameters such as density, yarn pitch, tension, and fiber type. Two structures were created: a plain jersey fabric (control) and a derivative with pores and surface reliefs to improve permeability and comfort. The DSR approach proved effective in systematizing the development of these structures, promoting the integration of theory and practice. Furthermore, the need to incorporate visual tools (such as 3D simulations) into textile design teaching was highlighted to improve communication between designers and technicians.
Keywords: spacer knitting; design science research; education; textile structures; epidermolysis bullosa